Armenian immigrants in Canada and their distribution in Montreal - Chichekian, Garo (Cahiers de géographie du Québec, 1977)
In many respects the characteristics of the process of Armenian immigration to Canada have not been significantly different from that of other ethnic groups. Political persecutions, and socio-economic stresses are identified as the main reasons for Armenian emigration. One noticeable difference, however, is present. It pertains to the number of places of origin which exceeds twenty. This is expected for a nation with 50% of its members living in diapora (the other 50% resides in the Soviet Union, and specifically within the Armenian S.S.R.). The pattern of distribution, on the island of Montréal showing a definite « concentration », has been also identified in other ethnic studies such as Greeks, Albanians, etc. Social, cultural, and ethnic factors attempting to explain such patterns of concentration are applicable in the case of the Armenians.